THE REGIONAL, THEORETICAL AND GENERAL STRATIGRAPHY AS TREATED BY THE INTERDEPARTMENTAL STRATIGRAPHIC COMMITTEE (ISC) - Zhamoida A.I.; Prozorovskaya E.L. (My University, 1996)
The 40 years of activity of the Interdepartmental Stratigraphic Committee (ISC) of Russia for the benefit of the regional stratigraphy in the country are briefly reviewed; the most significant results of the work of the ISC and its Commissions on the problems of theoretical and general stratigraphy are summarized for the first time. The estimated completeness of the stratigraphic studies is supplemented by a formulation of the key problems of regional stratigraphy that are common for many regions and require special research. The theoretical research in stratigraphy has included the object, subject and basic principles of science, problems of typization and classification, principles used in terminology, and criteria for the determination and correlation of the stratigraphic units and their boundaries. The results of this work were published in the two editions of Stratigraficheskii kodeks (Stratigraphic Code) issued in 1977 and 1992. The general stratigraphy covers the problems of unification of terminology and nomenclature, preparation of stratigraphic scales and schemes, unification of stratigraphic procedures, and elaboration of methods. Recommendations are given for theoretical research and for the study of the general problems of stratigraphy.